Jewish-Hellenistic biology in a gnostic treatise (Circe de clásicos y modernos, 2018)
The gnostic treatise on the Origin of the World narrates that the powers of the Archon shaped Adam but failed in the attempt to impress him with human form. The body was left soulless and abandoned for forty days until Sophia Zoe sent her breath into Adam. The treaty includes the Jubilee tradition and its chronology for the entry of Adam and Eve into Paradise: forty and eighty days, respectively. A mosaic precept about the presentation of the woman in the Temple and the biology of Hellenic Judaism found in Philo can be seen in the background of the story.
Keywords: Adam; Eve; gnostics; Jubilee; Philo of Alexandria